Modeling the impact of education on individual earnings: 2019 evidence from Sudan - Hussien, Hamid (Technium Social Sciences Journal, 2020)
The impact of education on individual earnings has not been adequately discussed in the Sudanese literature. This paper estimates the rate of return on education by modeling individual-level Sudanese survey data for 2019. The importance of these data lies in the fact that they represent the period of Islamist rule in Sudan, which spanned thirty years and ended in April 2019 as a result of a peaceful youth popular revolution. A secondary aim is to trace how demographic characteristics (marital status, gender, locale) affect individual earnings. Results show, on average, an additional year of education increases individual earnings 4% (4.4% for men, 9.2% for women). Marital status exhibits the largest impact on Sudanese individual earnings, with married respondents’ earnings 78.7% more than singles. Almost 90% of the variation in wages is determined by all levels of education, and trade pays the highest wage among surveyed occupations. Mincer models prove that the return on education was significantly positive for occupations in healthcare and electricity and significantly negative in real estate.